Dictionary of economics and business - Nemmers, Erwin Esser; Janzen, Cornelius Cicero (Paterson, N.J. : Littlefield, Adams, 1959)
This dictionary lists terms under their abbreviations. It is designed to include the terms commonly used in college courses in the following subjects: accounting, business law, etc.
ne 01/09/2021
Ref.
Keywords: Economics